CHARACTERIZATION AND ANALYSIS OF PEROVSKITE OXIDE Sr2FeCoO6 SYNTHESIZED BY GEL-COMBUSTION PROCESS - Durrani, S. K.; Hussain, N.; Saeed, K.; Ahmad, N.; Qazi, N. K.; Ahmad, M.; Siddique, M. (The Nucleus, 2010)
The microscopic and well-dispersed strontium iron cobalt based (SrFe0.5Co0.5O3) perovskite oxide powders have been synthesized by nitrate-citrate gel-combustion process with stiochiometeric composition variation of metal nitrate salts and citric acid. Crystallinity and phase analysis were performed by X-ray diffraction (XRD). Inspection of XRD patterns revealed that almost pure single phase SrFe0.5Co0.5O3 cubic Pm3m symmetry was obtained. Morphology of sintered specimens was examined by scanning electron microscopy (SEM). It was observed that grain size of sintered samples increases with calcination temperature. XRD and SEM observations revealed that the crystal formation and morphology of SrFe0.5Co0.5O3 oxide were dependent on the precursors and pH of precursor solutions. Thermal decomposition of gel precursor was investigated by thermogravimetric analysis (TG/DTA).57Fe Mössbauer spectroscopic studies on assynthesized and calcined specimens have confirmed the uniform dispersion of Fe3+ ions in the tetrahedral framework of SrFe0.5Co0.5O3.